2013
DOI: 10.1007/s00405-013-2499-8
|View full text |Cite
|
Sign up to set email alerts
|

Natural evolution of an eardrum bridge in patients with a traumatic eardrum perforation

Abstract: Although the “eardrum bridge” of traumatic tympanic membrane perforations (TMPs) is very little seen, the underlying natural evolution during the healing process are still unknown.The aim of this retrospective study was to evaluate the natural evolution of the “eardrum bridge” of TMPs. The data for 36 patients with barotrauma-associated traumatic TMPs with an “eardrum bridge” between January 2006 and December 2007 were retrieved. The eardrum bridge was completely liquefied due to infection in one patient. The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Temporal bone houses many vital structures, involvement of these structures in temporal bone fractures is possible in road traffic accident including blunt trauma, laceration, avulsion of the part or whole of the pinna with tympanic membrane perforation. [12][13][14][15][16][17] CONCLUSION: Overall healing in all the patients with traumatic perforations with either conservatively (90%) spontaneous healing or with myringoplasty (10%) groups were 100%. It is very common in day-to-day life and the highest incidence is by slap and Road Traffic Accident, that too in males age group between 20-30 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…Temporal bone houses many vital structures, involvement of these structures in temporal bone fractures is possible in road traffic accident including blunt trauma, laceration, avulsion of the part or whole of the pinna with tympanic membrane perforation. [12][13][14][15][16][17] CONCLUSION: Overall healing in all the patients with traumatic perforations with either conservatively (90%) spontaneous healing or with myringoplasty (10%) groups were 100%. It is very common in day-to-day life and the highest incidence is by slap and Road Traffic Accident, that too in males age group between 20-30 years of age.…”
Section: Discussionmentioning
confidence: 99%
“…A dry graft may become wet after insertion into the middle ear if bleeding develops at the perforation edges and in the middle-ear mucus. During spontaneous healing of traumatic tympanic membrane perforations with eardrum bridges, Lou found that a few bridges gradually became necrotic and merged into the newly healed eardrums 32 . In addition, when a dry graft is placed in the wet physiological environment of the middle ear, it will shrink and lose contact with the remnant margins of the tympanic membrane under which it is tucked, especially anteriorly, and cause graft failure 33 …”
Section: Tympanoplasty Outcomementioning
confidence: 99%